Structural and ultrastructural analysis of embryonic development of Prochilodus lineatus (Valenciennes, 1836) (Characiforme ; Prochilodontidae) - Ninhaus-Silveira, Alexandre; Foresti, Fausto; de Azevedo, Alexandre (Cambridge University Press, 2006)
This survey was performed to characterize the embryogenesis of Prochilodus lineatus. Seven stages of embryo development were identified - zygote, cleavage, blastula, gastrula, segmentation, larval and hatching - after a period of incubation of 22h (24 degrees C) or 14h (28 degrees C). The following cleavage pattern was identified: the first plane was vertical (2 blastomeres); the second was vertical and perpendicular to the first (4 blastorneres); the third was vertical and parallel to the first (4 x 2); the fourth cleavage was vertical and parallel to the second (4 x 4); the fifth was vertical and parallel to the first (4 x 8); and the sixth cleavage was horizontal (64 blastomeres). At the blastula stage (3.0-4.0 h (24 degrees C); 1.66-2.0h (28 degrees C) irregular spaces were detected and periblast structuring was initiated. At the gastrula stage (4.0-8.0 h (24 degrees C); 3.0-6.0 h (28 degrees C) the epiboly, convergence and cell movements, as well as the formation of embryonic layers, had begun. The segmentation stage (10.0-15.0h (24 degrees C); 7.0-10.0h (28 degrees C)) was characterized by a rudimentary formation of organs and systems (somites, optic vesicle and intestinal delimitation). The embryo at the larval stage (16.0-21.0 h (24 degrees C); 11.0-13.0 h (28 degrees C)) showed a free tail, more than 25 somites, an optic vesicle and a ready-to-hatch larval shape. The blastomeres at cleavage stage had disorganized nuclei indicating high mitotic activity. At gastrula, the blastomeres and the periblast had euchromatic nuclei and a large number of mitochondria and vesicles. The yolk was organized into globose sacs, which were dispersed into small pieces prior to absorption.
Keywords: Characiforme; embryo; embryogenesis; Prochilodus lineatus; teleost